2018
DOI: 10.1088/1742-6596/1049/1/012023
|View full text |Cite
|
Sign up to set email alerts
|

Work-related Musculoskeletal Disorder (WRMD) among Production Operators: Studies of Differences in Age and Gender

Abstract: Abstract. Prevalence of musculoskeletal pain is a major concern among manufacturing-based companies as they are still very reliant on manual labour. A better understanding whether musculoskeletal pain differ between gender and would enable organizational intervention to improve employees' health and safe working conditions. Therefore, the objective of this study is to determine the current prevalence of musculoskeletal pain among production workers and differences of musculoskeletal pain between gender and acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…(3) crouching down on the floor; (4) pulling out a duty bin and putting the item into the bin; (5) placing the bin back to the initial position.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) crouching down on the floor; (4) pulling out a duty bin and putting the item into the bin; (5) placing the bin back to the initial position.…”
Section: Methodsmentioning
confidence: 99%
“…Manual material handling (MMH) is one of the main factors contributing to WMSDs among workers in industrial developing countries such as Malaysia [4]. Furthermore, most companies in Malaysia do not practice ergonomic guidelines since such guidelines have not been legislated [5].…”
Section: Introductionmentioning
confidence: 99%
“…There was a significant difference in participants in Australia who reported experiencing work-related musculoskeletal pain across the categories of age and sex. Work-related musculoskeletal problems are common among different work groups, and studies have shown a higher prevalence among female [24][25][26] and older [27][28][29] workers.…”
Section: Work-related Musculoskeletal Pain and Fatiguementioning
confidence: 99%